Evaluasi Pengolahan Air Limbah Domestik dalam Meningkatkan Kinerja Sanitasi (Studi Kasus Kecamatan Kebomas, Gresik) - Sa'dy, Mohammad Arsyad; Soedjono, Eddy Setiadi (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2026)
The Kebomas District in Gresik Regency faces challenges in optimizing sanitation services through communal Wastewater Treatment Plants (WWTP). This study aims to evaluate the technical effectiveness of domestic wastewater treatment at three locations—KPP Karangmas, KPP Sejahtera, and KPP Sentosa—to improve regional sanitation performance. A quantitative descriptive method was employed by analyzing influent and effluent quality, as well as operational parameters such as Organic Loading Rate (OLR) and Hydraulic Retention Time (HRT). The results show that effluent concentrations for critical parameters exceeded the quality standards set by the Ministry of Environment and Forestry Regulation No. 11 of 2025, with ammonia levels ranging from 14.2–15.1 mg/L and fecal coliform reaching 11,000 MPN/100 mL. Removal efficiencies for BOD and COD varied significantly; KPP Karangmas showed the best performance with a COD removal efficiency of 72%, while KPP Sejahtera and KPP Sentosa only achieved 40-55, far below the 80% design target. This low efficiency is attributed to extreme underloading conditions, where the actual organic load was only 11-34% of the design capacity. In conclusion, WWTP performance is not yet optimal due to inappropriate influent organic loading and the lack of disinfection units and adequate aeration systems. Technical recommendations include modifying the system into an intermittent anaerobic-aerobic process to effectively reduce ammonia levels.